Implementing communication technologies to enhance learning efficiency at a technical vocational education and training college in Cape Town - Godwin P. Dzvapatsva; Edmore Chinhamo; Bingwen Yan; Courage Matobobo (Academy of Cognitive and Natural Sciences, 2024)
This paper explores the impact of extending instructional time at technical vocational education and training (TVET) colleges using WhatsApp's mobile social network (MSN) application. In South Africa, there is relatively little discussion on extending instructional time within the TVET sector, yet instructional time loss is consistently mentioned as one of the most significant challenges. During the study, the subject of Computer Programming was examined in light of poor learner performance. This study employed mixed-methods research following a pragmatic paradigm to formulate educational policies potentially dealing with TVET instructional time losses in South Africa. Data were collected from two TVET centres (FB1 and FB2) involving two lecturers and 48 students in Cape Town. Despite the study's mixed results, qualitative data reflected the need to extend instructional time and improve the efficiency of applications like WhatsApp. Quantitative data reflected an overall percentage pass rate of 56% and 100% for FB2 and FB1, respectively. The messaging application, however, has challenges, such as disrupting conversations. By participating in learner WhatsApp groups, the paper believes lecturers can reap positive benefits from these initiatives. This study adds voice to mixed-method practices. To maximise pedagogical efficiency, this study recommends that educators provide practical guidance on using MSN applications to increase instruction time.